Netiquette concept at the assessment of college student social competence with TOPSIS method - Rianto Rianto; Sri Mulyani (Compiler, 2021)
Social competence of students college is important during the process of implementing the practicum, from social competence we can find out capable the students are in several ways such as the ability to collaborate, speak in forums, reduce social conflicts in the environment, make a network and much more. In this study, it provides a model solution for assessing social competence in students college when carrying out practicum. The purpose of the study was to develop an assessment model by measuring students' social competence during the implementation of the practicum. The number of correspondents in the study was 78 students taken from the number of practicum students in Aerospace Engineering. The data analysis technique uses the TOPSIS method, where the results of this study will obtain the best ranking of 78 KP students who have the highest social competence value. The model of the assessment can be used by lecturers of the Aerospace Engineering, Adisutjipto Aerospace Technology Institute during the practicum process or after. With this assessment model, the advantages of the Adisutjipto Aerospace Technology Institute can synergize in creating graduates with a global and humanistic character.